Pergeseran Sosial Budaya Masyarakat Sungai: Sebuah Pembacaan Sosiologi Sastra Terhadap Cerita Pendek “Jukung” Karya Zulfaisal Putera - Titik Wijanarti (Balai Bahasa Kalimantan Tengah, 2020)
The river is one important part that is so attached to the life of the Banjar people of South Kalimantan from time to time. This study analyzes a literary work that also discusses the life of the Banjar community related to river life, namely a short story titled